Designing a Collaborative Learning Platform Based on Learnersourcing and Gamification - Alexandru Smarandache; Elvira Popescu (Interaction Design and Architecture(s))
In traditional, old-fashioned educational settings, students are passive consumers of learning content and do not actively contribute to the overall improvement of the learning process. While the situation has been changing lately and novel teaching approaches have been proposed, there are many educational systems in which the problem still persists. In this context, we introduce an innovative educational platform called ShaLe, which aims to provide comprehensive support for learnersourcing and gamification. More specifically, the ShaLe system allows students to share additional educational resources alongside those provided by the teachers. It features an integrated question-answer system to facilitate discussions and clarifications related to the teacher’s materials. Additionally, the platform introduces a dedicated task that encourages students to create new assignments and evaluate solutions proposed by their peers. Furthermore, students can visualize their own performance metrics and can earn badges for exceptional achievements, adding a gamification component to the learning process. As such, the platform is designed to facilitate collaborative learning among students, stimulate learner engagement, while also decreasing the workload of the teacher.